Geodatabases in design: a floodplain analysis of Little Kitten Creek - Castle, Eric E. (Kansas State University, 2007)
This study is an integration of GIS, the Arc Hydro data model and tools, and hydrologic models to solve land use planning issues in the Little Kitten Creek watershed, Riley County, Kansas. Every day designers plan and design in watersheds. These designs alter the land use cover and change the hydrologic regime. Generally the design and development process does not consider upstream/downstream impacts on water quality and quantity. As a result development often increases flooding and water pollution. With the advent of the geodatabase, and the Arc Hydro geodatabase data model, designers have a flexible new tool for rapid simulation of a watershed. Arc Hydro allows the incorporation of traditional hydrologic data into linked modeling software together enabling users a “one-stop” approach for assimilating and modeling water resource systems. Once hydrologic data is in the Arc Hydro format it can be incorporated into assessment models, such as the Map to Map model. This case study assessed the floodplain analysis capabilities of the Map to Map model in the Little Kitten Creek (HUC 14) watershed. Steps to accomplish this goal were: data collection (digital and field surveys) and processing, geodatabase construction, linking the geodatabase with hydrologic modeling programs and, analysis of land uses within the watershed using the Map to Map model with the intent to produce flood maps based on land use changes.
Keywords: Arc Hydro; flood plain analysis; map to map; landscape architecture; Hydrology (0388); Landscape Architecture (0390); Urban and Regional Planning (0999)